2011
DOI: 10.1017/s1751731110002521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the prebiotics inulin and lactulose on intestinal immunology and hematology of preruminant calves

Abstract: Prebiotics are suggested as an alternative to antibiotics in animal rearing. Fermentable substances such as inulin or lactulose have been proposed to stimulate the immune system and health by modulation of the intestinal flora and its fermentation products. In this study, effects of inulin and lactulose on the intestinal health and hematology of calves have been investigated. Both prebiotics significantly decreased thrombocyte counts in peripheral blood. Only inulin was able to increase hemoglobin concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 46 publications
2
20
0
1
Order By: Relevance
“…Thus, the kids in EG could receive the daily dose of inulin. In previous studies with young livestock such as calves (Heinrichs et al, 2003;Hill et al, 2008;Masanetz et al, 2011), lambs (Thayne, 2007;Milewski et al, 2010) and pigs (Davis et al, 2004;Lynch et al, 2007), prebiotics were added to milk replacer or concentrate feed of suckling or weanling animals. However, prebiotics have not been supplemented to animals sucking milk from their dams through oral gavage.…”
Section: Management and Experimental Designmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the kids in EG could receive the daily dose of inulin. In previous studies with young livestock such as calves (Heinrichs et al, 2003;Hill et al, 2008;Masanetz et al, 2011), lambs (Thayne, 2007;Milewski et al, 2010) and pigs (Davis et al, 2004;Lynch et al, 2007), prebiotics were added to milk replacer or concentrate feed of suckling or weanling animals. However, prebiotics have not been supplemented to animals sucking milk from their dams through oral gavage.…”
Section: Management and Experimental Designmentioning
confidence: 99%
“…Verlinden et al (2006) reported that 3% inulin added to the diet did not change blood neutrophil, lymphocyte and monocyte concentrations and haematocrit value in dogs. Masanetz et al (2011) reported no change in the total WBC count, blood neutrophil, lymphocyte and monocyte concentrations of calves fed the diet containing 2% inulin. The results of Verlinden et al (2006) and Masanetz et al (2011) were in agreement with those of our study.…”
mentioning
confidence: 94%
See 3 more Smart Citations